Katalog Foto Toko Djadjan Apel Malang sebagai Media Informasi - Dimas Adi Saputra; Handry Rohmad Dwi Happy (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2021)
Located in Jalan Melati number 50 Kavling E Malang, Djajan Apel Malang Store which was established in 2016 has a vintage-themed concept providing several kinds of Malang souvenirs that are often in demand by tourists, one of which is the hallmark of this shop, apple cake and classic cake. Currently, visitors and buyers must open the packaging first to find out each variant flavor. In addition, the information for other variant is less detailed. Based on these weakness, to make it easier for visitors and buyers to find out bout variants, prices, composition, netto, and length of storage, a photo catalog will become the one of the printed media that placed at the Toko Djadjan Apel Malang to make visitors and buyes easier find the variant. From the questionnaires of 30 respondents, as much as 89,24% stated that the selection of photo catalog media are strongly agreed and was in accordance with the target market so that whit the exsistence of this photo catalog, the problem formulation was answered. Keywords: Toko Djadjan Apel Malang, Catalogue, Photo, Media, Information